2017
DOI: 10.2135/cropsci2016.07.0636
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Tolerance Indices Useful for Drought Tolerance Selection in Smooth Bromegrass

Abstract: In smooth bromegrass (Bromus inermis Leyss), few efforts have been made to develop rapid and reliable physiological indices for selection of persistent and drought‐tolerant genotypes. In addition, the association of these indices with seasonal growth activity, such as summer dormancy and autumn recovery, has not been studied. In this research, 36 genotypes of smooth bromegrass were clonally propagated and evaluated under water stress and nonstress conditions during 2013 to 2014. Water stress greatly influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Compared with autoclaved medium, the activities of the antioxidant enzymes POX, CAT and SOD increased in seedlings cultured on media with ≤29.3 μM CD, and decreased significantly in media sterilized with 88.0 μM CD ( P < 0.05). This is in accordance to the physiological responses of plants to other environmental stressors, such as hydrogen peroxide 33 , lower temperature 34 and drought 35 . MDA, one of the end products of stress-induced lipoperoxidation of polyunsaturated fatty acids, is an important index that can indicate the function and integrity of the plant cell membrane 3638 .…”
Section: Discussionsupporting
confidence: 83%
“…Compared with autoclaved medium, the activities of the antioxidant enzymes POX, CAT and SOD increased in seedlings cultured on media with ≤29.3 μM CD, and decreased significantly in media sterilized with 88.0 μM CD ( P < 0.05). This is in accordance to the physiological responses of plants to other environmental stressors, such as hydrogen peroxide 33 , lower temperature 34 and drought 35 . MDA, one of the end products of stress-induced lipoperoxidation of polyunsaturated fatty acids, is an important index that can indicate the function and integrity of the plant cell membrane 3638 .…”
Section: Discussionsupporting
confidence: 83%
“…ese morphological traits have extensively been used for the screening of germplasm [44][45][46][47]. But the present research has proved that these morphological traits are less 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 Proline 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 effective than the biochemical traits for the rice germplasm screening against drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that, on average, water stress reduced seed and forage yield by 38 and 14%, respectively, suggesting a higher impact of drought on reproductive growth than vegetative growth of smooth bromegrass genotypes. In a 2-year field drought study with 36 smooth bromegrass genotypes selected from 25 half-sib polycross progenies, drought overall reduced dry matter yield of smooth brome genotypes by 36 and 39%, relative to non-drought control in 2013 and 2014 (Saeidnia et al, 2017b). Reduction of dry matter yield in bromegrass under drought stress can be explained by reduction in photosynthetic capacity as evidenced by drought-caused reduction in photosynthetic pigments and relative water content.…”
Section: Effects Of Drought On Forage Yield and Qualitymentioning
confidence: 96%
“…These mechanisms are likely to be important under drought and/or heat stress as insufficient water or impaired metabolism impedes full utilization of light energy leading to higher oxidative damage to photosynthetic machinery (Mittler and Zilinskas, 1994;Niyogi, 1999). Photoprotective carotenoids and wax are therefore correlated with drought tolerance of crop plants, including bromegrass (Saeidnia et al, 2017b), and these traits can be measured using canopy/leaf reflectance data derived from high-throughput hyperspectral imaging (Penuelas and Filella, 1998). Higher photoprotective capacity generally contributes to increased quantum efficiency of photosystem II, which can be measured using highthroughput imaging chlorophyll fluorescence.…”
Section: Phenotyping For Abiotic Stress Tolerance and Resource Use-efmentioning
confidence: 99%